Adams's outline of fractures, including joint injuries - Hamblen, David L. (Churchill Livingstone Elsevier, 2007)
The 12th edition of the now classic Adam's Outline of Fractures - prepared by authors working in the UK - has been updated to include the latest conservative and surgical approaches to the management of fractures. Suitable for medical undergraduates and trainee surgeons, as well as nurses and physiotherapists working in trauma services, this classic text continues to offer a sound basis for the safe and effective management of musculoskeletal injuries.